Correlation between cervical vertebrae maturation stage and midpalatal suture maturation stage in population aged 8-19: an observational analytic study - Novliana, Shelly; Wijaya, Harryanto; Arifin, Sariyani Pancasari Audry; Kit, Yeoh Chiew (Padjadjaran Journal of Dentistry, 2025)
ABSTRACT Introduction: One of the treatments for malocclusion, especially class II and class III cases often associated with maxillary constriction, is Rapid Maxillary Expansion (RME). Successful RME treatment requires evaluation of the Midpalatal Suture Maturation Stage using Cone-Beam Computed Tomography (CBCT). However, CBCT entails increased cost and radiation exposure. Meanwhile, the Cervical Vertebrae Maturation Stage serves as a biological indicator of skeletal growth. This study aims to analyze the correlation between Cervical Vertebrae Maturation Stage and Midpalatal Suture Maturation Stage. Methods: This study used an observational analytic research design with a consecutive sampling method. Secondary data of cephalogram and CBCT images of 47 subjects aged 8–19 years were analyzed. CVMS was assessed using the Baccetti method, while MPSMS was evaluated using the Angelieri method. The Spearman rank correlation test was applied to assess the correlation between the two variables. This research was conducted at the Department of Orthodontics, Faculty of Dentistry, Trisakti University from September to December 2024. Results: A distribution of MPSMS stages (A to E) corresponding to increasing CVMS stages (CS1 to CS5). Spearman correlation analysis revealed a strong and highly significant positive correlation between CVMS and MPSMS, with a correlation coefficient of r=0.640 and p=0.001, consistent across the entire sample and within gender subgroups. Conclusion: There is a strong correlation between CVMS and MPSMS in the population aged 8–19 years.KEYWORDS Cervical vertebrae, midpalatal suture, maturation stage, palatal expansion technique